Resíduos da indústria de beneficiamento de pimenta rosa (Schinus terebinthifolia Raddi): perfil químico e atividade antimicrobiana de extratos contra bactérias hospitalares - Gomes, Rodrigo Borges de Araujo (2019)
Schinus terebinthifolia Raddi is a plant used in folk medicine in the treatment of various diseases and has several biological potentials. Its fruit is used as condiment and has high demand in the spice market. In the present study extracts prepared from residues from the pink pepper processing industry were characterized chemically by gas chromatography/mass spectrometry (GC-MS) and Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). The antibacterial activity of the extracts was evaluated against multidrug-resistant strains of hospital origin (Staphylococcus aureus, Enterococcus faecium, Enterococcus faecalis, Pseudomonas aeruginosa and Acinetobacter baumannii) and standard strains (ATCC). The apolar fractions presented triterpenes as main components and the polar extracts were characterized by high contents of phenolic compounds, especially gallotannins, gallic acid and flavonoids. The methanolic fraction and the hydroethanolic extract of the residues were the most active mainly against S. aureus (MIC 0.60 – 0.90 mg/mL), E. faecium and E. faecalis (MIC 1.20 – 2.10 mg/mL). These results demonstrate the richness of bioactive compounds present in the residues and indicate a possible application of this material for the development of biotechnological products with potential against multidrug resistant bacteria.